1972
DOI: 10.1042/bj1260193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate availability on lipogenesis in sheep

Abstract: 1. Lipogenesis in sheep liver and adipose tissue was investigated by incorporation studies in vitro with radioactive glucose and acetate and by assays of key enzymes. 2. Carbohydrate availability to sheep was increased by feeding on a diet containing 70% soluble carbohydrate, by infusing glucose into the abomasum or by direct intravenous infusion of glucose. 3. Under these conditions lipogenesis from glucose and acetate was increased from very low values in lìver and adipose tissue, especially in those animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

1974
1974
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 21 publications
0
40
0
2
Order By: Relevance
“…Increased glucose availability in the diet and intravenous, intra-abomasal or intra-duodenal glucose infusion all result in increases in fatty acid synthesis from glucose and lipogenic enzyme activity in sheep liver and adipose tissue (Ballard et al 1972 Lactate has been reported to be a significant lipogenic precursor for fatty acid synthesis in both sheep and cattle adipose tissue (Prior, 1978;Whitehurst et al 1978). The negligible incorporation of radioactivity from [ ~-'"Cllactate into fatty acids suggests that the route of metabolism is via pyruvate dehydrogenase (Vernon, 1980a) and this is supported by the results of which show that lactate is converted to fatty acids via citrate; the latter authors suggest that the activities of ATP-citrate lyase and malate dehydrogenase (oxaloacetatedecarboxylating) (NADP+) are not rate-limiting in the conversion of lactate to fatty acids.…”
Section: -10%mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased glucose availability in the diet and intravenous, intra-abomasal or intra-duodenal glucose infusion all result in increases in fatty acid synthesis from glucose and lipogenic enzyme activity in sheep liver and adipose tissue (Ballard et al 1972 Lactate has been reported to be a significant lipogenic precursor for fatty acid synthesis in both sheep and cattle adipose tissue (Prior, 1978;Whitehurst et al 1978). The negligible incorporation of radioactivity from [ ~-'"Cllactate into fatty acids suggests that the route of metabolism is via pyruvate dehydrogenase (Vernon, 1980a) and this is supported by the results of which show that lactate is converted to fatty acids via citrate; the latter authors suggest that the activities of ATP-citrate lyase and malate dehydrogenase (oxaloacetatedecarboxylating) (NADP+) are not rate-limiting in the conversion of lactate to fatty acids.…”
Section: -10%mentioning
confidence: 99%
“…The lack of utilization of glucose in fatty acid biosynthesis is reflected in the very low specific activities of ATP-citrate lyase, malate dehydrogenase (oxaloacetate-decarboxylating) (NADP+) and pyruvate dehydrogenase in ruminant tissues (Ballard et al 1972; Robertson et al 1980). …”
Section: -10%mentioning
confidence: 99%
“…Le métabolisme des lipides dans le foie de ruminant a été décrit par Rémésy et al (1984, 1986 Ballard, 1967Ballard et al, 1969Ballard et al, , 1972Hood et a/., 1972 ; Ingle et al, 1972a, b ;Vézinhet, 1976 ;Liepa et al, 1978 ;Prior, 1978 ;Smith et Crouse, 1984 …”
unclassified
“…These known effects are coherent with the increase in plasma glucose and insulin concentrations observed in the present study in steers fed maize silage compared with cut grass and could result in higher lipogenic enzyme and LPL activities in AT. Indeed, although glucose is of minor importance as a carbon source for FA synthesis, the oxidation of glucose via the pentose phosphate pathway is an important source of reduced NADP, whereas its oxidation via glycolysis contributes to 3-glycerol phosphate for FA esterification in ruminant AT (Ballard et al, 1972;Janes et al, 1985). It could thus be hypothesized that lipogenic potential (as measured in vitro) was increased by glucose and insulin in the maize silage group and/or decreased by PUFA in the grass-fed groups, but that this potential was not expressed in vivo because of the management of animals at similar growth rates.…”
Section: Discussionmentioning
confidence: 99%